Psychosocial distress and cardiovascular disease. (13th November 2019) - Natt och Dag, Y; Mehlig, K; Rosengren, A; Lissner, L; Rosvall, M
Abstract: Background: The contemporary increase in psychological distress observed in many countries is, by itself, a public health issue of great concern. Methods: This prospective study aims to investigate the impact of psychological distress on incident cardiovascular disease, in different age groups and also with respect to sex, among participants in the Gothenburg-based InterGene Study cohort. This cohort comprises a total of 3614 men and women, aged 25-75 years. Included in the present study were individuals who were free of previous CVD diagnoses and who fully completed all baseline examinations. Inclusions took place during 2001-2004. Psychological distress at baseline was assessed by self-rating depression and anxiety scales. A wide range of physiological and behavioral parameters were also assessed, which allowed for relevant adjustments. The outcome was incident CVD, and with a 12 year follow-up. Cox-regression analyses were performed. Results: The results showed an increased risk of incident CVD with higher scores on each of the scales. The majority of the findings persisted after adjustments for relevant confounders. It was most common for young women to score high on the anxiety and depression scales. Conclusions: The associations between psychological distress and later life cardiovascular disease calls for enhanced public health measures aiming at ameliorating psychological health, not least in younger age groups. Key messages: There was an increased risk of incident CVD with higher scores on psychosocial distress scales. The majority of the findings persisted after adjustments for relevant confounders.